PELATIHAN MANAJEMEN PEMASARAN BAGI PETAMBAK BIBIT IKAN LAUT DI DESA BANDING-KEC. RAJABASA LAMPUNG SELATAN - M. Tony Nawawi; Darryl Darryl; Jennifer Dinata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The purpose of carrying out community service in Banding-Rajabasa Village, South Lampung, is to explain how important it is for the farmer group to know the role of knowledge about Marketing Management, and to map and provide the best solution that will be implemented in the village.